The democratic aspects of trade union recognition - Bogg, Alan (Hart Pub., 2009)
The long ascendancy of pluralism and 'collective laissez-faire' as a guiding ideology of British labour law was emphatically shattered by the New Right ideology of Thatcher and Major. When New Labour was finally returned to power in 1997, it did not, however, attempt to resurrect the pre-Thatcher preference for pluralist non-intervention in collective industrial relations. Instead, it purported to follow a 'Third Way'. A centrepiece of this new approach was the statutory recognition provision, introduced in Schedule A1 TULRCA 1992. By breaking with the tradition of voluntarism in respect of re.